Improvement of Renz's Active Band-Pass Filter Using Uniformly Distributed RC Circuit - Sorapong Wachirarattanapornkul; Vanvisa Chutchavong; Pornsak Attavunich; Pongpan Rattanathanawan; Sudasawan Ngammongkolwong; K. Janchitrapongvej (My University, 2024)
This paper presents the improvement of Renz’ s active band-pass filter. We proposed two types of band-pass filter. The first type of filter circuit structure, resembles to Renz's band-pass filter. The circuit comprising a single gain amplifier and three uniformly distributed RC network (URC). The second type band-pass filter circuit configuration consists of a gain amplifier with one URC and a double capacitive layer (DURC). From the experimental results, it is showed that the behavior of the proposed band-pass filter gives good narrow bandwidth, high $Q$ and low sensitivities compared to the Renz's filter.
Keywords: Analog and Mixed-Signal Circuit Design; Photonic and Optical Devices; Advanced MEMS and NEMS Technologies